2019
DOI: 10.3390/atmos10120791
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bulk Composition on the Heterogeneous Oxidation of Semi-Solid Atmospheric Aerosols

Abstract: The OH-initiated heterogeneous oxidation of semi-solid saccharide particles with varying bulk compositions was investigated in an atmospheric pressure flow tube at 30% relative humidity. Reactive uptake coefficients were determined from the rate loss of the saccharide reactants measured by mass spectrometry at different monosaccharide (methyl-β-d-glucopyranoside, C7H14O6) and disaccharide (lactose, C12H22O11) molar ratios. The reactive uptake for the monosaccharide was found to decrease from 0.53 ± 0.10 to 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Since OH radicals are highly reactive, the reactive uptake of OH radicals by OA species and subsequent effects on the particles’ optical properties, hygroscopicity, and cloud condensation nucleus (CCN) activity have been extensively studied. ,, Several experimental studies have examined the effect of particle viscosity on the OH reactive uptake, where particle viscosity is modulated by RH or organic composition. ,,, For example, Slade and Knopf observed that γ (the fraction of colliding OH radicals that lead to reaction) of OH and levoglucosan (LEV) increases by a factor of 3 as RH increases from 0 to 40%, which is attributed to enhanced diffusivity as LEV gradually deliquesces with increasing RH . Davies and Wilson also reported that increasing RH from 20 to 50% lowers the viscosity of citric acid (CA) from 2 to 0.2 Pa s, thereby enhancing the OH reactivity by about a factor of 3.…”
Section: Introductionmentioning
confidence: 99%
“…Since OH radicals are highly reactive, the reactive uptake of OH radicals by OA species and subsequent effects on the particles’ optical properties, hygroscopicity, and cloud condensation nucleus (CCN) activity have been extensively studied. ,, Several experimental studies have examined the effect of particle viscosity on the OH reactive uptake, where particle viscosity is modulated by RH or organic composition. ,,, For example, Slade and Knopf observed that γ (the fraction of colliding OH radicals that lead to reaction) of OH and levoglucosan (LEV) increases by a factor of 3 as RH increases from 0 to 40%, which is attributed to enhanced diffusivity as LEV gradually deliquesces with increasing RH . Davies and Wilson also reported that increasing RH from 20 to 50% lowers the viscosity of citric acid (CA) from 2 to 0.2 Pa s, thereby enhancing the OH reactivity by about a factor of 3.…”
Section: Introductionmentioning
confidence: 99%
“…When diffusion is not the rate limiting step, thermodynamic equilibrium is reached and the composition of the air−water interface is governed by the surface−bulk partitioning properties of the solutes. 13,32,33 Surfactants with long alkyl chains have been detected in atmospheric aerosols and are known to accumulate at the surface. 3,34,35 Smaller, more hydrophilic molecules and ions also display surface−bulk partitioning leading to a solute concentration gradient close to the air−water interface.…”
Section: Introductionmentioning
confidence: 99%
“…In multicomponent particles, even though the solutes are dilute enough to neglect intermolecular interactions, concentration gradients near the surface lead to solute reactive uptake coefficients that are different from those observed in a single component particle. 32 A better understanding of the effect of composition on the chemical fate of aerosols under oxidative conditions therefore requires a systematic investigation of the effect of the organic functional groups on heterogeneous reactivity. Amides and saccharides are good archetypal molecules for investigating such effects as they display a very wide range of partitioning properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations